Will the recovery continue? Four fragile markets, four years later - Greg Hannsgen; Dimitri B. Papadimitriou (Levy Economics Institute of Bard College, 2011)
In this brief, Research Scholar Greg Hannsgen and President Dimitri B. Papadimitriou focus on the risks and possibilities ahead for the US economy. Using a Keynesian approach and drawing from the commentary of other observers, they analyze publicly available data in order to assess the strength and durability of the expansion that probably began in 2009. They focus on four broad groups of markets that have shown signs of stress for the last several years: financial markets, markets for household goods and services, commodity markets, and labor markets. This kind of analysis does not yield numerical forecasts but it can provide important clues about the short-term outlook for the country's economic well-being, and cast light on some longer-run threats. In particular, dangers and stresses in the financial and banking systems are presently very serious, and labor market data show every sign of a widespread and severe weakness in aggregate demand. Unless there is new resolve for effective government action on the jobs front, drastic cuts in much-needed federal, state, and local programs will become the order of the day in the United States, as in much of Europe.
Keywords: 330